Strategy for cooling of computing data center facilities - Sulaiman, S.A. (2019)
This chapter reports a study on the optimum cooling energy required in operating a campus grid outside normal working hours. The main issue involved in this study includes assurance of acceptable operating air temperature for the computers in the data center facility (laboratories) when the air-conditioning system is turned off. At the same time, the study looks into minimizing the cooling energy required to overcome the heat dissipated from the CPUs, and thus ensuring conservation of energy. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2019.